Response to case studies of eco-regional approaches at the farm/enterprise level - Fernández Rivera, S.; Hiernaux, Pierre H.Y.; Kaufmann, Ralph R. von; Turner, M.; Williams, Timothy O. (Kluwer Academic Publishers, 1995)
Three papers are reviewed in this paper. The first paper presents a model of biological processes to investigate long-term effects of soil and crop long-erm effects of soil and crop management strategies while the other two papers present approaches to study crop production strategies at the enterprise and farm levels. The papers indicate that eco-regional research needs to be broad enough to cover analysis at the micro, meso and macro levels. Realism dictates that a solid foundation is needed at the lower levels before issues at the macro level are addressed. The challenge is to be able to assess accuately the amount of resources and division of labour between research partners need to or refine the available knowledge at the lower levels, without necessarily compromising work at the macro level. These papers highlight the importance of well-focused in terdisciplinary work in eco-regional activities.